Integration of Technological Pedagogical Content Knowledge (TPACK) Learning Methods in The Learning Management System as An Effort to Improve Educator Competence - Iskandar, Didik (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
Educators as a type of profession are also required to have a certification of expertise. It is stated in Permendikbud No. 16 of 2007 that one of the competencies that must be possessed by an educator is proficiency in using information technology in the teaching and education process. The TPACK method is one method that is considered capable of boosting the competence of educators. The TPACK method can be optimally implemented if it is supported by good learning system management. Therefore, it is necessary to integrate the TPACK learning method with the learning management system. This study aims to describe the planning and design of the integration of the TPACK learning method into the management of the education system in Indonesia as an effort to increase the competitiveness of the workforce, especially workers in the education sector. The research method used is descriptive qualitative method with a literature study approach. The data used is secondary data derived from scientific publications. The results show that the core components of the TPACK method consist of technology, pedagogy, and content. These three components can intersect and synergize so as to create new conditions of understanding. TPACK requires educators to have a complete understanding related to technology operations and the use of technology in learning, demands to continue to develop pedagogical abilities, and increase educator competencies through increasing literacy and understanding of the field of study to be taught.